In-Silico Studies of Potential Anti-Alzheimer Compounds from Spondias dulcis - Fathoni, Ahmad; Salma, Aninda; Amilia, Nurul; Rudiana, Tarso (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Alzheimer's is a chronic neurodegenerative disease characterized by low levels of acetylcholine and the accumulation of abnormal neuritic plaques, leading to rapid memory decline and cognitive impairment. Compounds found in the kedondong plant (Spondias dulcis) have been reported to exhibit in vitro activity as acetylcholinesterase inhibitors. This study examines the potential of active compounds in Spondias dulcis in their interaction with acetylcholinesterase, an enzyme implicated in the pathogenesis of Alzheimer's disease. The enzyme was obtained from the Protein Data Bank (PDB ID: 4EY7). The test ligands were screened based on Lipinski's rule and docked with the receptor. The results of molecular docking which yielded the five best affinity energy values were followed by ADMET testing (absorption, distribution, metabolism, excretion, and toxicity). The test ligand ellagic acid deoxyhexoside showed binding energy at -11.213 kcal/mol. Molecular dynamics simulations were performed using YASARA with AMBER14 force fields for 50 ns. The test ligand ellagic acid eoxyhexoside showed an MM-PBSA value of -51.277 kcal/mol and exhibited good complex stability with an average total RMSD value of 2 Å and low inter-residue fluctuation values. These findings are consistent with the results obtained from the comparator ligand, donepezil. Therefore, compounds in Spondias dulcis have the potential to act as acetylcholinesterase inhibitors and can be considered for the development of therapies for Alzheimer's disease.